LANDSLIDE HAZARD ASSESSMENT APPROACH ON THE PROVINCIAL ROAD IN EAST JAVA - Emil Wahyudianto (Journal Innovation of Civil Engineering (JICE), 2021)
Landslide hazard mapping on the road infrastructure has 2 (two) main sources. The first is through a landslide inventory survey, and the second is through recording data on past landslide events. Each of the methods above has advantages and disadvantages. The most appropriate moment in making a landslide hazard map is when a certain disaster strikes an area with a certain measured impact. The Unpredictable variables that have been hidden and difficult to predict will be eliminated. Disaster events in disaster-prone mapping become a key variable as well as a validator. The characteristic of the landslide on road is also very specific, depends on the nature of the vehicle's spatial movement, and the scope of the affected area which is narrow but extends along the slopes coincide with the road. The most appropriate disaster mapping in measuring the level of hazard, vulnerability, and risk on the road is based on landslide record data. That is because the variables used to predict landslide events are extremely varied and too many are unknown. Assessing a map using a landslide disaster occurrence on the road is easier than making a map through the calculation method of certain variables that are overlapped. Based on the calculation of frequency analysis for 12 years, the daily rainfall value of 126.2 mm per day is the threshold of rain which has a probability of a landslide of 95% on the road infrastructure in East Java Province.